2007
DOI: 10.1007/s10802-007-9131-6
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder and Behavioral Inhibition: A Meta-Analytic Review of the Stop-signal Paradigm

Abstract: Deficient behavioral inhibition (BI) processes are considered a core feature of attention deficit/hyperactivity disorder (ADHD). This meta-analytic review is the first to examine the potential influence of a wide range of subject and task variable moderator effects on BI processes--assessed by the stop-signal paradigm--in children with ADHD relative to typically developing children. Results revealed significantly slower mean reaction time (MRT), greater reaction time variability (SDRT), and slower stop-signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
364
7
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(395 citation statements)
references
References 70 publications
22
364
7
2
Order By: Relevance
“…More recent functional imaging evidence has also supported Posner and Petersen's three-module framework and started to link these brain findings to genetic influences (Fan et al, 2003(Fan et al, , 2005Fan and Posner, 2004). Certainly, the selection-foraction influence (Holroyd, 2004), directly or indirectly, was evident in many subsequent papers involving a large variety of motor response selection tasks relevant to ADHD, including modality-specific motor choice (Paus et al, 1993), motor control/monitoring, and/or willed action (Badgaiyan and Posner, 1998;Liddle et al, 2001;Luu et al, 2000;Picard and Strick, 2001;Turken and Swick, 1999), Stroop and Stroop-like tasks Pardo et al, 1990), and tasks involving the over-riding or inhibition of prepotent responses such as go/no-go, stop-signal, or countermanding tasks (Alderson et al, 2007;Aron et al, 2003;Durston et al, 2003a;Ito et al, 2003;Kawashima et al, 1996). Although lacking in the full, necessary precision desired for a complete mechanistic account of attention, selection for action helped pave the way for studies trying to link brain processes with attention and ADHD.…”
Section: Cognitive Neuroscience Influences Relevant To Adhd Researchmentioning
confidence: 99%
“…More recent functional imaging evidence has also supported Posner and Petersen's three-module framework and started to link these brain findings to genetic influences (Fan et al, 2003(Fan et al, , 2005Fan and Posner, 2004). Certainly, the selection-foraction influence (Holroyd, 2004), directly or indirectly, was evident in many subsequent papers involving a large variety of motor response selection tasks relevant to ADHD, including modality-specific motor choice (Paus et al, 1993), motor control/monitoring, and/or willed action (Badgaiyan and Posner, 1998;Liddle et al, 2001;Luu et al, 2000;Picard and Strick, 2001;Turken and Swick, 1999), Stroop and Stroop-like tasks Pardo et al, 1990), and tasks involving the over-riding or inhibition of prepotent responses such as go/no-go, stop-signal, or countermanding tasks (Alderson et al, 2007;Aron et al, 2003;Durston et al, 2003a;Ito et al, 2003;Kawashima et al, 1996). Although lacking in the full, necessary precision desired for a complete mechanistic account of attention, selection for action helped pave the way for studies trying to link brain processes with attention and ADHD.…”
Section: Cognitive Neuroscience Influences Relevant To Adhd Researchmentioning
confidence: 99%
“…The STOP task has been used in many studies of ADHD children to evaluate inhibition deficits (see reviews by Lijffijt et al (2005), Oosterlaan et al (1998), and Willcutt et al (2005)). A recent review (Alderson et al, 2007) contrasted the es for the Stop-signal reaction time (SSRT, es ¼ 0.63) and mean RT (MRT, es ¼ 0.45), as well as on a measure of Stop Signal Delay (SSD) defined as the difference between them (ie, SSD ¼ MRTFSSRT, es ¼ À0.025), and concluded that children with ADHD had slower and more variable RTs to primary stimuli (ie, go-stimuli) as well as a Stop signal, and thus they appeared to have 'yan underlying attention deficit rather than deficient inhibitory control' (p 755). Studies that combined the STOP task with fMRI also showed differential activation patterns of a distributive nature, which do not support models that hinge on the dysfunction in any one frontal subregion (Dickstein et al, 2006).…”
Section: Cognitive Deficitsmentioning
confidence: 99%
“…1 Functional neuroimaging studies of response inhibition have typically implicated 2 networks. A frontostriatal network consisting of the inferior frontal gyrus, presupplementary motor area and basal ganglia is involved in controlling and executing the response inhibition process, 2 and a frontoparietal network consisting of the superior frontal gyrus and parietal lobe has been suggested to be important for attentional processing and top-down control of behaviour.…”
Section: Introductionmentioning
confidence: 99%